THE EFFECT OF EDIBLE COATING CHITOSAN-VIRGIN COCONUT OIL ON THE STORAGE OF STRAWBERRY - Eviomitta Rizki Amanda; Yulianto Ade Prasetya; Alliyu Wahyu Mardini; Berta Dhea Nabila (Jurnal Penelitian Pascapanen Pertanian, 2021)
Edible coating based on chitosan-virgin coconut oil (VCO) as coating materials on strawberries have been successfully developed. This research aims to prolong the shelf life of strawberries by inhibiting the growth of microorganism. The experimental design used completely randomized design (CRD). Edible coating solution was prepared by mixing chitoson 1,6% b/v and VCO in various concentration namely 1%, 2% and 3%. The immersion process was carried out by inserting strawberries into edible coating solution for 1 min, 2 min and 3 min, respectively. The results showed that edible coating with various of VCO concentrations have good performance to inhibit the growth of microorganism and fungi. The variotion of VCO concentration 2% on the seventh day storage was more effective at inhibiting bacterial growth of 37,5% with the total colony growth of 1,52 × 109 cfu/mL. The optimum immersion time showed that 2 min has optimum inhibition results of 64,9% with the total colony growth of 4,7 × 108 cfu/mL on the second day of storage. Whereas for yeast, the optimum VCO concentration of 1% on the seventh day of storage showed the best inhibition performance for yeast growth of 72% with the total colony growth of 4,9 × 108 cfu/mL. The duration of immersion process showed the greatest inhibition performance of 70,8% on the seventh day with the total colony growth of 5,1 × 108 cfu/mL. Edible coating chitosanVCO successfully inhibited the microorganism growth and maintain the strawbeeries quality until the fifth day of storage.